‘O London, London’: mid-Tudor literature and the city - Jones, Mike Rodman (Oxford University Press, 2017)
This article explores the ways in which mid-Tudor writing addressed and imagined the city of London. Scholarly reactions to mid-Tudor writing have been mixed: where nineteenth-century editors were drawn to the anti-urban aspect of these texts, later criticism has tended to denigrate it on ethical or aesthetic grounds. This article joins recent efforts to reassess the qualities of Tudor writing by focusing on its highly emotive imagining of the city. It focuses on a ‘cross-section’ of mid-Tudor literature, including poetry, prose, and sermons, all produced in the period c.1542–c.1550. These number works by Robert Crowley, Henry Brinklow, Hugh Latimer, Henry Howard, Thomas Lever and John Bale. I argue that mid-Tudor writing was persistently drawn to represent England’s capital in particular ways. The imagined urban landscapes of this writing are strongly biblical in nature, partly because of the continued significance of biblical rhetoric and figures in the religious landscape of the time. However, mid-Tudor writing can also be seen to focus consistently on images of the urban poor, and use a rhetorical technique of satire by listing which blurs distinctions between forms of religious and commercial invective. This sub-genre of Tudor writing also needs to be understood in terms of its rich literary debts to earlier, particularly medieval, forms of urban writing. The latter part of the essay focuses on two such debts: those of Henry Howard to Petrarch’s ‘Babylonion Sonnets’ in the Canzoniere, and of Robert Crowley to William Langland’s Piers Plowman.